Mengatasi Perilaku Membolos Peserta Didik Menggunakan Konseling Individual - Busmayaril, Busmayaril; Umairoh, Efi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2018)
Counseling service activities can be organized either individually or in groups. Individual counseling services are conducted through individual counseling, while group by group counseling. Individual counseling is directed to learners to help correct inadequate habits / deviant behavior (truancy behavior) in order to become better behaviors in the school environment. The results of pre-research surveys that the authors obtain in Senior High School (SMA) Pangudi Luhur Bandar Lampung indicate that there are still learners who do pelanaggaran school rules (ditching). The method used in this research is field research (field research) with the type of descriptive research. The population in this study were students of class XI and 1 counseling teacher, from the total of students of class XI, the writer took 7 students plus 1 teacher guidance and counseling to be sampled in this research. Data collection techniques used interview, observation and documentation method, while to analyze data used qualitative data analysis method using inductive and deductive thinking approach. Based on the processing and analysis of data that the authors do in this thesis is known that the implementation of individual counseling services occur mostly based on BK teacher initiative is by calling learners, other than that the condition of facilities and infrastructure are inadequate to conduct individual counseling. Therefore, BK teachers should master the knowledge of the field of technical counseling and the steps that will be implemented, so that the implementation of individual guidance and counseling services in the school goes well and maximally